A posição de Marx frente ao direito nos escritos de 1835-1843 - Murilo Leite Pereira Neto (2018)
This presentation intends to make explicit the position of the young Marx towards right in the writings produced from 1835 to 1843, prior to his withdrawal to 'the study office' at Kreuznach, where he produced his first direct critique of Hegel's philosophy. We sought to apprehend such a position from the evolutionary movement of his intellectual acquisitions during the following period, proceeding with the immanent reading of the author's texts from school writings, through the most academic moment of Marx, when he studied law at the Universities of Bonn and Berlin, dropping out to finally obtain his doctorate in Philosophy from the University of Jena, to the journalistic articles published in Anekdota and Rhenish Newspaper - the democratic paper. At no other time in Marx's intellectual itinerary was law as important as at this point, especially from 1837 to March 1843. The word right [Recht] appears only in lesser amount than State [Staat], although mentioning the centrality of law in these writings sounds inadequate, since it is rather its recognition by the modern State - one that minimally corresponds to the idea of the State. From the Letter to the Father (1837) to the journalistic writings, a road that goes hands down through the doctoral thesis, we discover a thought in full development, which, after liberating itself from the idealism nourished by the philosophies of Kant and Fichte, landed in the objective philosophy of Hegel, with whom it related critically and reflexively. In this way, as a vigorous wanderer, Marx criticizes Jurisprudence and its limited character, as it proves incapable of apprehending right in the actual reality itself, falling back on dogmatism. Our author also demonstrates to be critic to natural law while defending rational law, recognized and positivized by the Rational State, the only one capable of reconciling form and content in the time of general laws